Child and Adolescent Development for Medical Learners: Developmental Neurobiology - Florence Eddins-Folensbee; Sheila Renee Martinez; Jason Scott Klein; Roland Wickes Folensbee (Association of American Medical Colleges, 2012)
Abstract This module entitled Developmental Neurobiology focuses on the brain as the body organ of emotions. Neural structures and systems of the social brain are reviewed using charts and graphs. Key neurodevelopmental characteristics and processes are reviewed and subcortical structures central for processing social/affective information, the amygdala and hippocampus, are compared and contrasted. In this module, the interplay of emotions and memory is highlighted and explored in the three clinical vignettes where "neurobiological hypothesis" are generated and used to guide resolution. This submission is one of six modules which can be used together as a complete course or independently by topic. Each module uses teaching tools which include learning objectives, lecture outline lecture text, clinical correlations or case vignettes, sample test questions, recent related research, after-class exercises or activities, audiovisual aids including some dedicated teaching clips or transcripts, bibliographies, and PowerPoint presentations. The authors believe that this curriculum has been crafted to appeal to medical learners who may not always appreciate what they see as "soft science". We believe that the effectiveness of our materials can be largely credited to this multimedia approach which is "made real" using video clip examples, after-class activities and exercises, and supplemental "special interest" dinner discussion groups.